Impact of Liquefied Natural Gas Exports on the Nigerian Exchange Rate: An ARDL Cointegration Approach, 2000 to 2021 (American Journal of Applied Statistics and Economics, 2023)
This study aimed to investigate the impact of liquefied natural gas (LNG) exports on the exchange rate of Nigeria. The investigation employed an autoregressive distributed lag model (ARDL) methodology to analyse data spanning the years 2000 to 2021 using a biannual dataset. The empirical findings provided evidence of a statistically significant and positive influence of liquefied natural gas exports on the exchange rate. This is supported by the results obtained from the short-term analysis. The research results revealed no causal link between the exports of LNG and the exchange rate in Nigeria. The study concludes that LNG exports cause the Naira to depreciate. The research suggested that the government should actively endorse and facilitate the expansion of non-oil and gas sectors, including agriculture, manufacturing, and services, to cultivate a more varied export portfolio. Moreover, adequate reserves can be used to stabilize the Naira during periods of volatility caused by fluctuations in LNG exports or other external factors.